The Influence of Work Environment, Organizational Justice, and Internal Communication on Employee Loyalty of Security Personnel At PT. Karuni Security Service - Abdul Halim; Murtasiyah Murtasiyah; Bintang Chairunnisa (Interdisciplinary Social Studies, 2026)
An abstract is often presented separately from the article, so it must be able to This research aims to analyze the influence of the work environment, organizational fairness, and internal communication on the loyalty of security personnel at PT. Karunia Security Service Balikpapan. The research method used was quantitative with a sample of 166 respondents obtained through census techniques. Data analysis was carried out through validity, reliability, classical assumption test, multiple linear regression, t-test, F test, and coefficient of determination. The results of the study showed that partially the work environment had a significant positive effect on loyalty, organizational fairness had a significant positive effect on loyalty, and internal communication had a significant positive effect with the most dominant influence on the loyalty of security personnel. Simultaneously, all three variables had a significant effect on loyalty, with a contribution of 61.1% (R² = 0.611). These findings underscore the importance of good working conditions, fairness in organizational policies, and effective internal communication in increasing employee loyalty.